A cross sectional study on cervical cancer and its prevention among women of age group 25- 50 years in a rural area of south Tamilnadu, India. - Nelson, Sudhir B.; Viswanathan, Naveenkumar; Jenifer, Nisha A.; B., Priyanka (International Journal Of Community Medicine And Public Health, 2018)
Background:Cancer of uterine cervix is one of the common carcinoma among females. India accounts for about 20% of cervical cancers. Prevention of cervical cancer, whether primary or secondary requires active participation of the community. For this they need knowledge about the disease & its prevention. Hence a study to assess the knowledge, attitude and practice regarding cervical cancer and its prevention was undertaken. Methods:A cross-sectional observational study was conducted in a panchayat area of Kanyakumari district, South Tamilnadu. A sample of 100 women aged 25-50 years was taken by multistage random sampling. Results:Only 68 women were aware of the existence of cervical cancer & Health workers were the most common source of information (41.2%). Those who were employed had more awareness though the differences were not statistically significant. Only 8 women (11.76%) knew that there is a vaccine to prevent cancer cervix. Among those who were aware of cervical cancer, only 47 (69.1%) knew about the existence of a screening test to detect cancer cervix. Only 8 women had undergone PAP smear. Among those willing to reveal the reason for not undergoing PAP smear, lack of time (15.38%), embarrassment (10.26%) and no facility (2.8%) were the reasons. Women who were employed were more likely to be aware about screening for cervical cancer (75%). Conclusions: The existence of cervical cancer has reached the awareness of majority of the women in our area. But specific knowledge about cervical cancer & its prevention is still lacking.